Pengaruh Latihan Individual Tactical Options With the Ball terhadap Menyerang Tim Futsal Putra UNJ - Zaidan Rizqi Setyabudi; Andri Irawan; Ruliando Hasea Purba (Mutiara : Jurnal Penelitian dan Karya Ilmiah, 2024)
This research aims to determine the effect of individual tactical options training with the ball on attacking the UNJ men's futsal team. This research uses quantitative research with experimental methods. Data collection was carried out at the 2024 Invitational Games Sports Championship and the 2024 Trofeo KSBF by providing treatment at FIK UNJ. The research population was 80 men's futsal athletes from KOP Soccer and UNJ Futsal. The sample taken using a purposive sampling technique was 14 people who competed in the 2024 Invitational Sports Games and Trofeo KSBF 2024 championships. The research instrument used was successful and failed research forms. The data analysis technique used is an observation technique using video recordings of UNJ futsal team matches. The results of Pre-test and Post-test data calculations in this study show that the Individual tactical options with the ball training has an effect on the level of attacking success in the UNJ men's futsal team with a tcount value of 6.88 which is greater than ttable 2.61 at a significant level. 0.05.